Parameter Extraction of PV Solar Cell: A Comparative Assessment Using Newton Raphson, Simulated Annealing and Particle Swarm Optimization - Rawat, Nikita; Thakur, Padmanabh (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*302.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.97146);" role="presentation">Proper modelling of PV cell is important to <span dir="ltr" style="left: calc(var(–scale-factor)*256.01px); top: calc(var(–scale-factor)*302.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90276);" role="presentation">calculate <span dir="ltr" style="left: calc(var(–scale-factor)*295.01px); top: calc(var(–scale-factor)*302.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954);" role="presentation">its <span dir="ltr" style="left: calc(var(–scale-factor)*308.09px); top: calc(var(–scale-factor)*302.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919844);" role="presentation">unknown parameters close to <span dir="ltr" style="left: calc(var(–scale-factor)*431.47px); top: calc(var(–scale-factor)*302.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902164);" role="presentation">the accurate values, <span dir="ltr" style="left: calc(var(–scale-factor)*515.62px); top: calc(var(–scale-factor)*302.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932477);" role="presentation">to <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*315.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90813);" role="presentation">attain <span dir="ltr" style="left: calc(var(–scale-factor)*99.14px); top: calc(var(–scale-factor)*315.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881658);" role="presentation">the I-V <span dir="ltr" style="left: calc(var(–scale-factor)*134.30px); top: calc(var(–scale-factor)*315.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905532);" role="presentation">characteristic <span dir="ltr" style="left: calc(var(–scale-factor)*192.65px); top: calc(var(–scale-factor)*315.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905232);" role="presentation">curve <span dir="ltr" style="left: calc(var(–scale-factor)*219.77px); top: calc(var(–scale-factor)*315.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.999315);" role="presentation">close to the hardware model. This can help for simulation, computing <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*328.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01122);" role="presentation">efficiency, maximum power point trac<span dir="ltr" style="left: calc(var(–scale-factor)*237.05px); top: calc(var(–scale-factor)*328.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.06332);" role="presentation">ing d<span dir="ltr" style="left: calc(var(–scale-factor)*260.09px); top: calc(var(–scale-factor)*328.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.88321);" role="presentation">esign, <span dir="ltr" style="left: calc(var(–scale-factor)*289.01px); top: calc(var(–scale-factor)*328.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950838);" role="presentation">optimization <span dir="ltr" style="left: calc(var(–scale-factor)*344.95px); top: calc(var(–scale-factor)*328.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954198);" role="presentation">and regulation <span dir="ltr" style="left: calc(var(–scale-factor)*410.59px); top: calc(var(–scale-factor)*328.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01318);" role="presentation">of PV system. This paper <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*341.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.869835);" role="presentation">estimates <span dir="ltr" style="left: calc(var(–scale-factor)*112.46px); top: calc(var(–scale-factor)*341.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930799);" role="presentation">single diode <span dir="ltr" style="left: calc(var(–scale-factor)*165.38px); top: calc(var(–scale-factor)*341.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921758);" role="presentation">PV model parameter<span dir="ltr" style="left: calc(var(–scale-factor)*249.77px); top: calc(var(–scale-factor)*341.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883571);" role="presentation">s such as <span dir="ltr" style="left: calc(var(–scale-factor)*290.33px); top: calc(var(–scale-factor)*341.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911732);" role="presentation">photocurrent, the saturation current, the series resistance, <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*355.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937774);" role="presentation">the shunt resistance and the ideality factor. The estimation is done by three different optimization methods for <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*368.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912553);" role="presentation">single-<span dir="ltr" style="left: calc(var(–scale-factor)*99.14px); top: calc(var(–scale-factor)*368.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921821);" role="presentation">diode model in an attempt to judge which method is <span dir="ltr" style="left: calc(var(–scale-factor)*311.45px); top: calc(var(–scale-factor)*368.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.874834);" role="presentation">surpassing <span dir="ltr" style="left: calc(var(–scale-factor)*356.23px); top: calc(var(–scale-factor)*368.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933957);" role="presentation">in terms of c<span dir="ltr" style="left: calc(var(–scale-factor)*406.99px); top: calc(var(–scale-factor)*368.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883888);" role="presentation">onvergence <span dir="ltr" style="left: calc(var(–scale-factor)*455.86px); top: calc(var(–scale-factor)*368.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942019);" role="presentation">time <span dir="ltr" style="left: calc(var(–scale-factor)*476.26px); top: calc(var(–scale-factor)*368.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912259);" role="presentation">and relative <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*381.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9459);" role="presentation">error. <span dir="ltr" style="left: calc(var(–scale-factor)*97.10px); top: calc(var(–scale-factor)*381.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.947265);" role="presentation">The first method Newton-<span dir="ltr" style="left: calc(var(–scale-factor)*203.33px); top: calc(var(–scale-factor)*381.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914596);" role="presentation">Raphson is a numerical method based on gradient descent approach, while the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*394.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.968026);" role="presentation">second and third methods are evolutionary methods, simulated annealing and particle swarm optimization <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*407.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.982864);" role="presentation">respectively. It <span dir="ltr" style="left: calc(var(–scale-factor)*139.22px); top: calc(var(–scale-factor)*407.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.947586);" role="presentation">was observed that <span dir="ltr" style="left: calc(var(–scale-factor)*221.09px); top: calc(var(–scale-factor)*407.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.982993);" role="presentation">particle swarm optimization algorithm <span dir="ltr" style="left: calc(var(–scale-factor)*387.43px); top: calc(var(–scale-factor)*407.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.976941);" role="presentation">is best among the methods and <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*421.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904719);" role="presentation">simulated annealing <span dir="ltr" style="left: calc(var(–scale-factor)*154.70px); top: calc(var(–scale-factor)*421.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895388);" role="presentation">showed the worse performance.